English language in the Malaysian education system: its existence and implications - Darmi, Ramiza; Albion, Peter (2013)
This article sets out to give a historical account of English language education programs in Malaysia as a foundation for understanding the existence of English language in Malaysia and its importance to Malaysian learners. The language background of Malaysians is very much tied up with the historical and educational background of the country. English is taught as a compulsory subject in schools despite the evolution of the Malaysian education system toward Bahasa Malaysia as the language of instruction. Since 1974, communicative language teaching has been proposed for the English language syllabus and it is an approach to engage learners in interaction and meaningful communication. However, differences between the school and university classrooms differentiate the language learning process. Malaysian learners who still have to learn English in universities need to develop a positive attitude for meaningful learning to occur.